Beyond Archaea: The Table Salt Bacteriome - Satari, Leila; Guillén, Alba; Latorre-Pérez, Adriel; Porcar, Manuel (Frontiers in Microbiology, 2021)
Commercial table salt is a condiment with food preservative properties by decreasing water activity and increasing osmotic pressure. Salt is also a source of halophilic Bacteria and Archaea. In the present research, the diversity of halotolerant and halophilic microorganisms was studied in six commercial table salts by culture-dependent and -independent techniques. Three table salts were obtained from marine origins: Atlantic Ocean, Mediterranean (Ibiza island) and Odiel marshes (supermarket marine salt); and other salts supplemented with mineral and nutritional ingredients were also used: Himalayan pink, Hawaiian black and one with dried vegetables known as Viking salt. Results of 16S rRNA sequencing reveal that the salts from marine origins display a similar archaeal taxonomy, but with significant variations among genera. Archaeal taxa Halorubrum, Halobacterium, Hallobellus, Natronomonas, Haloplanus, Halonotius, Halomarina, and Haloarcula, were prevalent in those three marine salts. Furthermore, the most abundant archaeal genera present in all salts were: Natronomonas, Halolamina, Halonotius, Halapricum, Halobacterium, Haloarcula and uncultured Halobacterales. Sulfitobacter sp. was the most frequent bacteria, represented almost in all salts. Other taxa such as Bacillus, Enterococcus and Flavobacterium were the most frequent taxa in the Viking, Himalayan pink, and black salts, respectively. Interestingly, the genus Salinibacter was detected only in marine-originated salts. A collection of 76 halotolerant and halophilic bacterial and haloarchaeal species was set by culturing on different media with a broad range of salinity and nutrient composition. Comparing the results of 16S rRNA metataxonomic and culturomics revealed that culturable bacteria Acinetobacter, Aquibacillus, Bacillus, Brevundimonas, Fictibacillus, Gracilibacillus, Halobacillus, Micrococcus, Oceanobacillus, Salibacterium, Salinibacter, Terribacillus, Thalassobacillus and also Archaea Haloarcula, Halobacterium, and Halorubrum were identified at least in one sample by both methods. Our results show that salts from marine origins are dominated by Archaea, whereas salts from other sources or salt supplemented with ingredients are dominated by Bacteria.